1987
DOI: 10.1302/0301-620x.69b3.3584195
|View full text |Cite
|
Sign up to set email alerts
|

Changes in local bone density after knee arthroplasty. The use of quantitative computed tomography

Abstract: Loosening is a serious problem in total arthroplasty and early detection of bone loss in the vicinity of an implant would help in its investigation. We present a method for the objective evaluation of bone adjacent to metallic implants in which a modified technique of quantitative computed tomography (QCT) is used to reconstruct cross-sectional images with few artefacts. We have used this technique in 19 patients with knee arthroplasties to monitor the changes in bone density around the tibial stem of the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 0 publications
3
16
0
1
Order By: Relevance
“…6(A)). For a group of 19 patients who had undergone cemented TKA, Seitz et al [33] reported that a loss in tibial bone density (measured by computed tomography) was stabilized after 1 year. Also similar to the results of our study, they found that the cortices near the stem had thinned.…”
Section: Discussionmentioning
confidence: 99%
“…6(A)). For a group of 19 patients who had undergone cemented TKA, Seitz et al [33] reported that a loss in tibial bone density (measured by computed tomography) was stabilized after 1 year. Also similar to the results of our study, they found that the cortices near the stem had thinned.…”
Section: Discussionmentioning
confidence: 99%
“…Ryd et al (29) stated that the cause of late-detected aseptic loosening in a total knee arthroplasty often might be traced back to factors acting in the early postoperative period. Even though the postoperative changes in bone density in the proximal tibia after total knee arthroplasty have been investigated in several studies (2,9,19,27,31), the extent of the bone remodeling and the mechanisms behind these changes are inconsistent. These divergent results can probably be explained by the use of different, few, and usually small areas for measurements of bone density, as well as the use of varying imaging techniques such as…”
mentioning
confidence: 99%
“…Most authors mention that bone mass loss following arthroplasty [6,9,12,15,18] stabilises after 1 year and then decreases [3,9,18]. Our study revealed a non-significant drop in BMD after 6 months in 80% of the areas studied in both knees, and that this was related to factors such as postoperative trophic disorders, reduced muscular activity and assisted loading.…”
Section: Discussionmentioning
confidence: 46%
“…The greatest changes in bone around porous implants occur during the 1st year after arthroplasty [3,9,16,18]. Knee bone mass decreases in the first 3 months, but does this 'fall-off' continue [6,12,13,15], or are the preoperative levels restored [3,9,18]?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation